Marco Caracciolo, The Experientiality of Narrative. An Enactivist Approach (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2014)
Review of Caracciolo, Marco. The Experientiality of Narrative. An Enactivist Approach. Berlin: De Gruyter, 2014. Print.